"A Christy Minstrel, a Harlequin, or an Ancient Persian"?: Opera, Hindustani Classical Music, and the Origins of the Popular South Asian "Musical". Issue 3 (September 2020) - Nicholson, Rashna Darius
Abstract : The story of South Asian colonial modernity and music offers up a multidirectional and polymorphous conceptual terrain featuring, among many agents, Hindustani royalty, touring minstrel and burlesque troupes, Jesuit missionaries and orientalists, and not least, social reformists. Nevertheless, scholarship on the history of Hindustani music consistently traces its development through classicization against the rise of Hindu nationalism while overlooking other palpable clues in the colonial past. This article argues for a substantial reevaluation of colonial South Asian music by positing an alternative and hitherto invisible auditory stimulus in colonial Asia's aural landscape: opera. Janaki Bakhle contends that "as a musical form, opera put down even fewer roots than did orchestral, instrumental Western classical music, " even though she subsequently states that "Western orchestration did become part of modern ceremonial activities, and it moved into film music even as it was played by ersatz marching bands." Bakhle further argues that Hindustani music underwent processes of sanitization and systematization within a Hindu nation-making project, a view that has been complicated by historians such as Tejaswini Niranjana. Niranjana describes how scholarship that focuses exclusively on the codification or nationalization of Hindustani music through the interpellation of a Hindu public neglects "sedimented forms of musical persistence." Not dissimilarly, Richard David Williams highlights how the singular emphasis on the movement of Hindustani music reform risks reducing the heterogeneous and complex musicological traditions in the colonial period to the output of a single, monolithic, middle-class "new elite." Previous scholarship, he argues, concentrates on "one player in a larger 'economy' of musical consumption." Following these calls for more textured perspectives on South Asian musical cultures, I suggest a somewhat heretical thesis: that opera functioned as a common mediating stimulus for both the colonial reinscription of Hindustani music as classical as well as the emergence of popular pan-Asian musical genres such as "Bollywood" music.